William H. Bridges, Digest of the Charters and Ordinances of the City of Memphis, from 1826 to 1867, Inclusive, Together with the Acts of the Legislature Relating to the City, with an Appendix Page 52, Image 52 (1867) Ordinances of the City of Memphis, Nuisance and Abatement Thereof, It is a public nuisance. -- § 5 - (:unkn) unknown (My University, 1867)
To carry on the business of manufacturing gun-powder or of mixing or grinding the materials therefor, in any building within eighty rods of any valuable building erected at the time such business may be commenced.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER